Bioattribution Needs a Coherent International Approach to Improve Global Biosecurity - Murch, Randall Steven (Frontiers in Bioengineering and Biotechnology, 2015)
The forensic investigation of hoax, suspected or actual biological weapons attacks and bioproliferation activities is recognized by biosecurity-advanced nations as an important pillar in a national biosecurity program. Some nations have taken this seriously; most others have not or are not aware of the potential. When law enforcement and forensic science investigations are performed in a coordinated manner, decisions assigning attribution are informed and accountability is supported through legal and policy decisions and actions. Incorporating public health investigative and tailored scientific assets makes the system even more effective, dynamic and robust. Perpetrators and enablers must be held at risk of being brought to justice, or through a policy decision resulting in direct action being taken or sanctions imposed. This paper provides a foundation and path forward to establish substantially expanded capability founded on establishing and leveraging national and regional programs and international agreement that attribution is an important component of biosecurity. Specific forward-looking initiatives will be recommended and discussed.